Efektivitas Media Pembelajaran Audiovisual Animaker dalam Meningkatkan Hasil Belajar dan Pemahaman Konsep IPA Siswa SMP - Zidan Afidah; Rusydiana Indra Safitri; Firdha Kusuma Ayu Anggraeni (Pendidikan Fisika Universitas Nurul Huda, 2023)
Low understanding of physics concepts has an impact on students' learning outcomes. The implementation of instructional media as a tool to support technology-based learning processes has the potential to be a solution. This research aims to determine the effectiveness of the Animaker audiovisual media in teaching physics. The type of research applied is quasi-experimental with a one-group pre and post-test design. The results of the initial test (pretest) and the final test (posttest) for the ninth-grade students at SMP Muhammadiyah 10 Bungah show a significant difference in learning outcomes with an N-Gain score of 0.71 (71%). Conceptual understanding reached a moderate category with a percentage of 57%. The student responses to the implementation of Animaker audiovisual media yielded an average score of 3.15, indicating that the media is engaging and suitable for use in teaching static electricity sub-material in everyday life (lightning phenomena)